Impact of autologous stem cell transplantation on long term renal function and associated progression-free and overall survival in multiple myeloma. Issue 13 (9th November 2020) - Abudayyeh, Ala; Lin, Heather; Mamlouk, Omar; Abdelrahim, Maen; Saliba, Rima; Rondon, Gabriela; Martinez, Charles S.; Delgado, Ruby; Page, Valda; Rajasekaran, Arun; Sanders, Paul W.; Qazilbash, Muzaffar
Abstract: The long-term impact of Autologous hematopietic stem cell transplantation (ASCT) on renal function, and the impact of renal function on progression-free survival (PFS) and overall survival (OS) in patients with multiple myeloma are not known. We retrospectively reviewed the records of 885 patients at our institution. We used linear mixed effect models to study the change in estimated glomerular filtration rate (eGFR) and a joint model approach to assess associations between the eGFR, PFS and OS. Sensitivity analyses were conducted at days 0, 100, 180, and 365 post-SCT. eGFR post-ASCT was significantly lower than at day 0 but stabilized at approximately 80 mL/min/1.73 m 2 . There was no association between eGFR and PFS or OS.; However, relapsed disease and ISS stage were associated with shorter PFS and OS. This data suggests that although there is a modest decline in eGFR post-ASCT, it is not associated with an adverse impact on PFS or OS. KEY POINTS: Advanced MM stage at diagnosis was associated with reduced eGFR at all stages of chronic kidney disease. eGFR was not associated with PFS or OS in any of the analyses, but disease-related factors prior to ASCT were all associated with reduced eGFR, PFS and OS. ASCT did not adversely impact kidney function and mitigated the risk of CKD on outcomes in MM.